Strategi Pembelajaran Mata Pelajaran Bahasa Jawa pada Anak Tuna Rungu-Wicara - Pudjastawa, Astrid Wangsagirindra; Bastian, Helmy; Kusweni, Rina (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Children with hearing impairments are children with special needs who have the same right to get education and develop according to their potential. Therefore they need different learning strategies to maximize their achievement in Javanese Subjects. This study aims to describe learning strategies that can be applied to deaf-speech-deaf children in the Javanese Language Subject as well as the existing inhibiting and supporting factors. In this field qualitative research which originated from observations, interviews, and supporting documents which were then strengthened by content analysis and triangulation it was found that effective learning strategies were those that were adapted to the individual needs of students, such as expository strategies, inquiry, contextual learning, and individualization. The restraints include a lack of parental support in banning Javanese material as well as the limited number of special teachers with Javanese teaching qualifications. However, supporting factors such as a comfortable learning environment, enthusiastic students, creative teachers, and school principals who support teaching and learning activities are very helpful in achieving success in Javanese Language Subjects for children who are deaf-mute. Therefore, this research has an important contribution to the development of more effective inclusive education for children with special needs.